HUBUNGAN ANTARA IMPLEMENTASI KUALITAS GOOD CORPORATE GOVERNANCE (GCG) DENGAN KINERJA PERUSAHAAN PADA INDUSTRI PERBANKAN - , Rina Lestari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Objectives of this research are: Knowing the significantcy relationship between implementation of quality Good Corporate Governance (GCG) with the performance of companies in.Indonesia banking industry. The research was conducted in the banking industry in Indonesia with a sample of as many as 54 conventional commercial banks from 122 banks in Indonesia since 2007 until 2010. The process of knowing the implementation quality of Good Corporate Governance (GCG) with the performance of companies in the banking industry using the chi-square test of the non-parametric statistical methods. Result of such referred research pointed out: (1) The test results show that there is a significant relationship between the quality of implementation of Good Corporate Governance (GCG) with the performance of companies in the Indonesian banking industry. (2) The results of the composite sample grouping of Good Corporate Governance (GCG) shows that from 2007 until 2010 most of the conventional commercial banks obtain a composite value GCG = 3 which means the implementation of good corporate governance quality is quite good. (3) the grouping of the composite sample bank soundness (TKS) showed that from 2007 until 2010 most of the conventional commercial banks obtain a composite value TKS = 3 which means the company's performance is quite healthy.